2018
DOI: 10.29252/ijrm.16.3.199
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supernatant product of adipose tissue derived mesenchymal stem cells and density gradient centrifugation preparation methods on pregnancy in intrauterine insemination cycles: An RCT

Abstract: Background: One of the most important involved factors in pregnancy occurrence following intrauterine insemination (IUI) is semen sample preparation. Recently, supernatant product of adipose tissue derived mesenchymal stem cells (SPAS) method has been shown to improve semen parameters. Objective: To compare the effect of preparation methods in order to IUI, SPAS and density gradient centrifugation (DGC). Materials and Methods:This trial was done on 80 couples with male factor infertility who attend jihad danes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The significant improvement in sperm parameters may be attributed to the numerous secreted bioactive factors mainly growth factors VEGF, granulocyte-colony stimulating factor (G-CSF), IGF-1, HGF, NGF, and FGF (13), anti- inflammatory cytokines IL-10 and transforming Growth Factor- β (TGF- β ) (13), and antioxidant defense constituents, more particularly superoxide dismutase (SOD) and catalase (20). Actually it was reported that VEGF, HGF, FGF2, NGF and IGF-1 were capable of maintaining and improving sperm motility by stabilizing sperm membrane proteins (2831).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant improvement in sperm parameters may be attributed to the numerous secreted bioactive factors mainly growth factors VEGF, granulocyte-colony stimulating factor (G-CSF), IGF-1, HGF, NGF, and FGF (13), anti- inflammatory cytokines IL-10 and transforming Growth Factor- β (TGF- β ) (13), and antioxidant defense constituents, more particularly superoxide dismutase (SOD) and catalase (20). Actually it was reported that VEGF, HGF, FGF2, NGF and IGF-1 were capable of maintaining and improving sperm motility by stabilizing sperm membrane proteins (2831).…”
Section: Discussionmentioning
confidence: 99%
“…As a promising therapy that warrants further investigation, the biological effects of CM of AD-MSCs on sperm quality were recently evaluated. However, methods of isolation and culture of AD-MSCs, and procedures of preparation of CM were not standardized, thus leading sometimes to inconclusive results (12, 13). Therefore, the aim of this study was to investigate the effect of AD-MSCs-CM on human sperm parameters, where oxidative stress levels and sperm vacuolization are being investigated for the first time.…”
Section: Introductionmentioning
confidence: 99%